ELECTRIFIACTION OF UZBEKISTAN: HISTORIOGRAPHY OF LAST PART OF XX AND BEGINNING OF XXI CENTURIES - Gulzora Nematjonovna Saidboboeva (American Journals Publishing, 2025)
Electrification as an important part of economic and industrial history and the historical process is being studied quite intensively by researchers. Many scientific literatures created at the end of the last and the beginning of this century contain information about electrification, which were studied directly in connection with socio-economic history. This article details their historiographical analysis.
Keywords: Historiography, research, electric power industry, industry, national economy.